2017
DOI: 10.5114/wiitm.2017.68547
|View full text |Cite
|
Sign up to set email alerts
|

The choice of optimal antireflux procedure after laparoscopic cardiomyotomy: two decades of clinical experience in one center.

Abstract: IntroductionTwo types of partial wrap are commonly performed in achalasia patients after Heller myotomy: the posterior 270° fundoplication (Toupet) and the anterior 180° fundoplication (Dor). The optimal type of fundoplication (posterior vs. anterior) is still debated.AimTo compare the long-term rates of dysphagia, reflux symptoms and patient satisfaction with current postoperative condition between two fundoplication groups in achalasia treatment.Material and methodsOur retrospective study included 97 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Two variables favored Toupet fundoplication compared to Dor procedure. A statistically significant shorter LOHS by 18 h was noted for Toupet compared to Dor based on 4 out of 7 studies [12–14, 16] (WMD 0.73, 95% CI 0.47 to 0.99, P < 0.0001) (Fig. 2), and QOL was found to be significantly better for Toupet compared to Dor based on two studies [12, 13] (WMD 1.68, 95% CI: 0.68 to 2.73, P < 0.001) (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Two variables favored Toupet fundoplication compared to Dor procedure. A statistically significant shorter LOHS by 18 h was noted for Toupet compared to Dor based on 4 out of 7 studies [12–14, 16] (WMD 0.73, 95% CI 0.47 to 0.99, P < 0.0001) (Fig. 2), and QOL was found to be significantly better for Toupet compared to Dor based on two studies [12, 13] (WMD 1.68, 95% CI: 0.68 to 2.73, P < 0.001) (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Rawling et al in the first RCT comparing Dor versus Toupet after HM [4] reported 41.7% of Dor patients to be affected by GER compared to 21% in Toupet, while Kiudelis et al [14] reported a similar result (35% Dor vs 11% Toupet). Torres‐Villalobos et al [12] the latest RCT to be published showed initially at 6 months a significant difference between the groups (7% Dor vs 34% Toupet), but at 24 months there was no statistical difference (10.5% Dor vs 31.5% Toupet).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 24 ] Several studies confirmed that a laparoscopic 270° Toupet or a laparoscopic 180° Dor fundoplication provided similar control of GORD at follow-up, with no difference in post-fundoplication symptoms, and majority of patients (88%) were satisfied with operation outcomes. [ 25 , 26 ] A retrospective review of prospectively collected data reported that incidence of recurrent HH increased in direct correlation with the preoperative HH size (No HH: 0%, small HH (<3-cm): 10.1%, large HH (≥3-cm): 16.6%, paraesophageal hernia (PEH): 20%, p 0.032) after magnetic sphincter augmentation. According to a 5-year observation, patients who underwent laparoscopic repair of large (≥5-cm) type III HH, the 5-year recurrence-free probability was similar, but an earlier failure rate was noted in the non-mesh group at 12 months (p .299).…”
Section: Discussionmentioning
confidence: 99%